A new method for phosphate purification for oxygen isotope ratio analysis in freshwater and soil extracts using solid‐phase extraction with zirconium‐loaded resin. (16th September 2022) - Ishida, Takuya; Kamiya, Hiroshi; Uehara, Yoshitoshi; Kato, Toshikuni; Sugahara, Shogo; Onodera, Shin‐ichi; Ban, Syuhei; Paytan, Adina; Tayasu, Ichiro; Okuda, Noboru
Abstract : Rationale: Phosphate (PO4 ) oxygen isotope (δ 18 OPO4 ) analysis is increasingly applied to elucidate phosphorus cycling. Due to its usefulness, analytical methods continue to be developed and improved to increase processing efficiency and applicability to various sample types. A new pretreatment procedure to obtain clean Ag3 PO4 using solid‐phase extraction (SPE) with zirconium‐loaded resin (ZrME), which can selectively adsorb PO4, is presented and evaluated here. Methods: Our method comprises (1) PO4 concentration, (2) PO4 separation by SPE, (3) cation removal, (4) Cl − removal, and (5) formation of Ag3 PO4 . The method was tested by comparing the resulting δ 18 OPO4 of KH2 PO4 reagent, soil extracts (NaHCO3, NaOH, and HCl), freshwater, and seawater with data obtained using a conventional pretreatment method. Results: PO4 recovery of our method ranged from 79.2% to 97.8% for KH2 PO4, soil extracts, and freshwater. Although the recovery rate indicated incomplete desorption of PO4 from the ZrME columns, our method produced high‐purity Ag3 PO4 and accurate δ 18 OPO4 values (i.e., consistent with those obtained using conventional pretreatment methods). However, for seawater, the PO4 recovery was low (1.1%), probably due to the high concentrations of F − and SO4 2− which interfere with PO4 adsorption on the columns. Experiments indicate that the ZrME columns could be regenerated and used repeatedly at least three times. Conclusions: We demonstrated the utility of ZrME for purification of PO4 from freshwater and soil extracts for δ 18 OPO4 analysis. Multiple samples could be processed in three days using this method, increasing sample throughput and potentially facilitating more widespread use of δ 18 OPO4 analysis to deepen our understanding of phosphorus cycling in natural environments.